A commuter-based two-step floating catchment area method for measuring spatial accessibility of daycare centers. (March 2015) - Fransen, Koos; Neutens, Tijs; De Maeyer, Philippe; Deruyter, Greet
Abstract: This paper puts forward a commuter-based version of the two-step floating catchment area (2SFCA) method, which has gained acceptance in studies on spatial health care accessibility. Current implementations of the 2SFCA method are static in that they consider centroid-based night-time representations of the population. The proposed enhancement to the 2SFCA approach addresses this limitation by accounting for trip-chaining behavior. The presented method is illustrated in a case study of accessibility of daycare centers in the province East Flanders in Belgium. The results show significant spatial differences in accessibility between the original and commuter-based version of the 2SFCA (CB2SFCA). They highlight the importance of giving heed to more complex travel behavior in cases where the need for detailed accessibility calculations is apparent. Highlights: Floating catchment area metrics use static representations of the population. Trip-chaining behavior is introduced in floating catchment metrics. The proposed commuter-based catchments account for daily mobility. A case study of accessibility of daycare centers in East-Flanders is elaborated. Results indicate significant differences between the 2SFCA and the proposed method.